A Reading Aloud Digital Application Based On An Android System Is Being Created By SMPN 2 Sidrap - Buhari Buhari; Andi Sadapotto; Ibrahim Manda; Sam Hermansyah (La Ogi : English Language Journal, 2021)
Reading aloud is frequently taught to junior high school students as a way of improving their English, particularly in the 7th grade. These factors make it imperative to perform research on creating an android-based reader digital application since technology could lead to engaging and effective teaching and learning methods. The study's objectives are to learn more about the process of creating an android-based reader digital application as a tool for teaching reading aloud to 7th grade students at SMPN 2 Sidrap and to determine whether such an application is practical. Research and Development (R&D) process by Borg and Gall, which included 10 steps, was utilized to develop the product. And because there is a limited amount of time and the product can only be developed in seven processes, it has been condensed to seven. the questionnaire-based observation. a method for gathering information from numerous validator expertise. Student survey data are used to determine effectiveness. The survey's findings reveal that the materials expert's overall score was 93.8% and that media experts' display layout and design received a score of 90%. 85% of the information from a poll of 30 students was collected. The outcome demonstrates that both teachers and students are in favor of using applications to aid in the acquisition of English. The pupils exhibit an interest in using the software as a virtual teacher assistant and feel more driven to study English using it.